A Multicriteria Index System for the Selection of Best Management Practices at the Watershed Scale - Chen, Lei; Xiao, Yuechen; Sun, Cheng; Xu, Jiajia; Shen, Zhenyao (Journal of Environmental Accounting and Management, 2026)
The selection of Best Management Practices (BMPs) is the key of nonpoint source pollution control at a watershed scale. To date, there are no comprehensive methods or corresponding tools for the selection of BMPs by considering the operation constraints on local spatial conditions, especially for those large-scale watersheds. In this study, a new method was developed to provide economically, ecologically and operationally effective solutions, which integrates the Geographic Information System-based multicriteria index analysis with a watershed model. Land use, area, soil type and slope were used as potential constraints for selection system. This method helps identify the potential placements for BMPs at the watershed scale and reduce the work of an accurate algorithm-based optimization of BMPs placement in watershed. The system was validated with Soil and Water Assessment Tool in Daning River watershed, the Three Gorges Reservoir Region, China. Based on the results, the new approach provides more speciﬁc potential sites for BMPs than traditional methods at a watershed scale. Within the new framework, the vegetative ﬁlter strip was suggested as the most widespread practice, while the constructed wetland is the least effective option. The area with relatively ﬂat agricultural plains was suitable for most practices, suggesting a more operationally effective scheme if the new method was used. The system developed in this study could easily extend to other watersheds to provide an objective selection method and the potentialsite of BMPs.